Certain Building Materials with Respect to Their Thermal Properties as Well as to Their Impact to Environment - Antonyová, Anna; Abdullah, Abd Halid; Nagapan, Sasitharan; Daud, Zawawi (International Journal of Integrated Engineering, 2018)
Thermal properties of certain building materials were studied with respect to environmental aspects. The building materials with significant insulation properties were laboratory tested using the special equipment based on Peltier module. During the experimental work, the samples of the following materials were tested: Expanded polystyrene (EPS), Autoclaved aerated concrete (AAC): Ytong, Calcium Silicate Board: Super-Isol and Foam glass (Cellular Glass Insulation): PERINSUL. The temperature was measured directly in connection of material with the Peltier module as well as in the distances of 5mm, 27.5mm, 50mm and 95mm from the Peltier module. The temperature taken at the surface of Peltier module reached -22°C, a typical temperature in the cold winter season. The results of the laboratory experimental work were modelled using the graphic representation. Modelling the thermal distribution will help to determine the ideal material thickness in the design of the building insulation.